Restaurante como lugar de hospitalidade e prestação de serviços: o Eat... Empório Restaurante - SILVA FILHO, Jose Neves da (2015)
This research tried to identify the factors that attract customers in choosing a restaurant. It was assumed that the convenience of several services available in one single place and the client hospitable treatment were key elements in attracting customers. A case study was conducted in São Paulo's Eat... empório restaurante, that offers grocery services, bar, wine cellar and cookery school. The restaurant manager, along with 123 customers, were interviewed. The results were analyzed using social representations' prototypical analysis methodology in order to determine the representation central core based on free evocation. It was found that the most important factor was quality, expressed as an intrinsic characteristic of the services offered, the following items were the menu and environment, which associated with Service, was considered as an expression of hospitality.